Genetic Diversity and Community Structure of Macrozoobenthos from Five Mangrove Forests in North Sumatra and Aceh, Indonesia - Anggita Amelati Harahap; Rizka Amelia; Ipanna Enggar Susetya; Arida Susilowati; Desrita Desrita; Tadashi Kajita; Mohammad Basyuni (Marine Science Department Diponegoro University, 2022)
Mangrove forests play an important role in macrozoobenthos ecology, assisting them in foraging, sheltering, and reproduction. In order to better understanding the genetic diversity and population genetic structure of macrozoobenthos, the mitochondrial 16S subunit (16S rRNA) gene was used. Present study aimed to determine genetic diversity and community structure of macrozoobenthos in the North Sumatra and Aceh mangrove forests, Indonesia. The reliaprep gDNA tissue miniprep system kit was used to extract 50 samples. To determine the PCR product's molecular weight, UVITEX software was employed. Genetic polymorphism was examined with GenAlex version 6.502, and each community underwent principal coordinates analysis (PCoA). MVSP 3.2.2 software and the unweighted pair group method with arithmetic mean (UPGMA) were used to construct the dendrogram. The 16S rRNA gene revealed a band size in the range of 370–500 bp. The PCoA showed that approximately all individual macrozoobenthos from each community structure were localized in the same quadrant. Genetic variation was varied by 3% between populations and 97.5% within individuals according to the analysis of molecular variance (AMOVA), with the dendrogram classifying the populations into two major clusters. Dendrogram analysis showed low genetic differentiation between macrozoobenthos populations of North Sumatra and the Aceh mangroves, implying the low ability of individuals in a population to adapt. The high polymorphic information content (PIC) value (0.886) reported was consistent with the number of alleles and size of the population's heterozygosity value. Present findings provide important information that will assist in formulation of mangrove conservation and restoration approaches.